Potential and Strategy for the Development of Pengelukatan Telaga Waja as a Religious Tourism Attraction in Kenderan Tourism Village, Gianyar - Suputra, Gusti Alit; Susanti, Herny; Premayani, Ni Wayan Wina (Universitas Pendidikan Nasional, 2023)
The development of religious tourism is used as an alternative to tourism development in the new normal era, including Kenderan Tourism Village. However, various technical problems still need to be solved in its operations and development efforts. This study aims to identify the potential and formulate a strategy for developing Pengelukatan Telaga Waja as a religious tourism attraction in Kenderan Tourism Village, Tegalalang, Gianyar. A type of qualitative descriptive research that identifies the potential and strategy of developing vehicle tourism villages as religious tourism by conducting observations and structured interviews on three informants selected by purposive sampling and meeting inclusion criteria. All results are interpreted using tourism area life cycle theory. As a result, the Pengelukatan Telaga Waja could be a religious tourism attraction in Kenderan Tourism Village, Gianyar District. The potential of the village with good natural resources and prioritizing elements of the sacred language, spirituality, and religion based on Balinese local wisdom makes Pengelukatan telaga waja favored by tourists. The results of the 4A analysis show that Pengelukatan Telaga Waja meets the attractive aspect (natural nuances that provide a sense of sacred mystique and still prioritize the religious side), amenities (there are facilities for post melukat meditation at Pancoran Solas), accessibility (road access to the Pengelukatan Telaga Waja site is quite good), and ancillary (the management of this Pengelukatan Telaga Waja place already has a management institution by Puri Figures). SWOT analysis shows that the Pengelukatan Telaga Waja meets all the criteria of a good SWOT as a religious tourism attraction in Kenderan Tourism Village, and improving the image of the area is the main development strategy.